One summer at Camp Winston - Shopsowitz, Karen (documentary : Moviewitz Productions Inc., 2010)
At Camp Winston, uniqueness truly is the norm. The camp accepts children with complex neurological disorders, that include Autism, Tourette Syndrome, and Asperger's Syndrome. Filmed against the backdrop of a beautiful Muskoka, Canada summer, these children, so often branded as different, are given the opportunity to grow a little, have a bit of fun, learn, and be embraced for exactly who they are. --